Immobilization of apricot pectinesterase (Prunus armeniaca L.) on porous glass beads and its characterization - Karakus, Emine; Pekyardimci, Sule (ELSEVIER, 2009)
Pectinesterase isolated from Malatya apricot Pulp Was covalently immobilized onto glutaraldehyde-containing amino group funcitonalized porous glass beads surface by chemical immobilization at pH 8.0. The amount of covalently bound apricot PE was found 1.721 mg/g glass support. The properties of immobilized enzyme were investigated and compared to those of free enzyme. The effect of various parameters such as pH, temperature, activation energy, heat and storage stability on immobilized enzyme were investigated. Optimum pH and temperature were determined to be 8.0 and 50 degrees C respectively. The immobilized PE exhibited better thermostability than the free one. Kinetic parameters of the immobilized enzyme (K-m and V-max values) were also evaluated. The K-m was 0.71 mM and the V-max was 0.64 mu mol min(-1) mg(-1). No drastic change was observed in the K-m and V-max values. The patterns of heat stability indicated that the immobilization process tends to stabilize the enzyme. Thermal and storage stability experiments were also carried out. It was observed that the immobilized enzyme had longer storage stability and retained 50% of its initial activity during 30 days. (C) 2008 Published by Elsevier B.V.
Keywords: Glass beads; Pectinesterase; Purification; Covalent immobilization; Characterization; Enzyme immobilization; SPECTROPHOTOMETRIC ASSAY; POLYPHENOL OXIDASE; ALPHA-AMYLASE; PECTINMETHYLESTERASE; EXTRACTION; Biochemistry & Molecular Biology; Chemistry